Students’ anxieties in speaking class - Mahyuzar Rahman (IJER (Indonesian Journal of Educational Research), 2016)
This qualitative research discussed the anxieties the students of semester 3, English Department, IAIN STS Jambi faced during the speaking class. The result of the research indicated that the causes of the students’ anxieties were the lack of grammar mastery, pronunciation problem, lack of vocabulary, unconfident feeling, fear of making mistakes and feared of being laughed by other students. But the dominant factors found were the lack of grammar, the lack of good pronunciation, and lack of vocabulary mastery. The lecturer had taken part to overcome these problems by giving them motivation not to give up easily, how to cope with vocabulary problems, and how to prepare well before coming into the class.